Context matters: How congruency of digital immersive environment and meal context affect consumer evaluations of plant-based products at two different levels of liking - Orr R; Giezenaar C; Godfrey AJR; Poggesi S; Hort J (Elsevier B.V., 2026)
Context can impact liking and emotional response, meaning traditional consumer testing methods lacking contextual cues may fail to reflect real-life assessments. As research on consumer acceptance of plant-based meat alternatives becomes increasingly popular, it is essential not to overlook the influence of context on acceptance. Using a within-subject design with 109 consumers, this study aimed to investigate whether affective response (liking and emotional response) to one liked and one disliked plant-based meatball alternative differed between i) a central location test (CLT) and two digitally recreated environments: one congruent (a home), one incongruent (classical music concert), and ii) products tasted alone and combined with tomato sauce. For both products adding sauce significantly increased liking (overall, appearance, flavour, and texture) (p < 0.001) and ratings for several positive emotions (p < 0.05). Notably, for the less-liked product, sauce addition had more impact on expected liking (t = 6.28, p < 0.001), appearance (t = 5.61, p < 0.001) and flavour (t = 2.28, p = 0.023) liking compared to the more-liked product. Comparing environments, only the disliked product had higher ratings for expected, appearance, and texture liking in the home compared to the concert and CLT (all p < 0.05). Regardless of the product, ratings for several positive emotions were higher (p < 0.05) in the congruent home than in the other environments. These results emphasise the need for product evaluations in contexts with greater ecological validity and indicate heightened sensitivity of a disliked meat alternative to contextual influences.
Keywords: Immersion; Context; Consumer testing; Emotional response; Plant-based meat alternatives; Congruency